2002
DOI: 10.1300/j172v02n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Training Tourism and Hospitality Managers in Universities

Abstract: The paper examines tourism and hospitality management training with a focus on an undergraduate tourism management programme, introduced in a Malaysian university. It assesses the overall effectiveness of the programme, in satisfying the institution's broad objectives, the needs and expectations of potential employers and that of the student. The paper identifies specific issues such as student admission policies, implementation of the practical industry training, divergent views on the value of the programme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the new millennia, a number of studies outside the Anglo-American context explored the challenges created from the introduction and implementation of internship programs in different cultural settings i.e. Australia (Richardson, 2008); Cyprus (Zopiatis, 2007); Greece (Christou, 1999); Hong Kong (Lam & Ching, 2007); Malaysia (Austin, 2002); Taiwan (Chen & Shen 2012); South Korea (Kim & Park, 2013); The Netherlands (Akomaning et al, 2011); Turkey (Collins, 2002). Despite the cultural dichotomy that divides the individualistic western world from the largely collective eastern cultures (van "t Klooster et al, 2008), a number of themes appear to be common in hospitality internship research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the new millennia, a number of studies outside the Anglo-American context explored the challenges created from the introduction and implementation of internship programs in different cultural settings i.e. Australia (Richardson, 2008); Cyprus (Zopiatis, 2007); Greece (Christou, 1999); Hong Kong (Lam & Ching, 2007); Malaysia (Austin, 2002); Taiwan (Chen & Shen 2012); South Korea (Kim & Park, 2013); The Netherlands (Akomaning et al, 2011); Turkey (Collins, 2002). Despite the cultural dichotomy that divides the individualistic western world from the largely collective eastern cultures (van "t Klooster et al, 2008), a number of themes appear to be common in hospitality internship research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…And that is what this research study is about. Austin (2002) examined tourism and hospitality programs in Malaysian universities that included practical industry training. It was found that Malaysian employers who provided training opportunities for hospitality students faced a general lack of commitment from interns and an inability or unwillingness to adapt to the requirements of the job.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other reasons may be difficulties in communication and in forming good relationships in the workplace (Collins, 2002; McMahon and Quinn, 1995), a topic that some authors include as aspects relating to coaching received during internships (Tse, 2010). Other alternatives are of a cultural nature (Austin, 2002). In this study, the cultural variables that could explain part of the differences were not considered, nor were the gender perspective and the country in which internships were completed, which could be related to the cultural aspects.…”
Section: Discussionmentioning
confidence: 99%